Intracoronary bone marrow cell application for terminal heart failure in children - Rupp, Stefan; Jux, Christian; Bönig, Halvard; Bauer, Jürgen; Tonn, Torsten; Seifried, Erhard; Dimmeler, Stefanie; Zeiher, Andreas M.; Schranz, Dietmar; Justus Liebig University Giessen (My University, 2012)
Introduction In spite of tremendous progress in the medical and surgical treatment of children with congenital heart disease and dilated cardiomyopathy achieved during the past few decades, for some children a heart transplant remains the only option. Clinically relevant benefits of intracoronary injection of autologous stem cells on cardiac function and remodelling have been demonstrated in adult patients with acute myocardial infarction. Experience with autologous stem cell therapy in children with severe congenital or acquired pump failure is limited to a small number of case reports. Method and results Between 2006 and 2010, nine severely ill children were treated with intracoronary infusion of autologous bone marrow-derived mononuclear cells as part of a compassionate therapy in our centre. No procedure-related unexpected adverse events occurred. There was one patient on extracorporeal membrane oxygenation who died of haemorrhage unrelated to the procedure; three patients proceeded to heart transplantation once a donor heart became available. The other five patients showed an improvement with respect to New York Heart Association classification (greater than or equal to 1), brain natriuretic peptide serum levels, and ejection fraction. Conclusion Similar to adults, intracoronary injection of autologous bone marrow cell is technically feasible and safe for children. On the basis of our data, we propose to perform a pilot study for children with congestive heart failure, to formally assess the efficacy of intracoronary autologous bone marrow cell therapy.
Keywords: ddc:610